Foreign direct investment - income growth for all? - Krüger, Ralf; Seith, Jennifer; Justus Liebig University Giessen (My University, 2005)
The United Nations declared halving the number of poor people by 2015 as the first of their eight Millennium Development Goals. Foreign direct investment (FDI) is often seen as one instrument towards this goal because of its ability to stimulate economic growth trickling down to the poor. Whereas many studies deal with those growth effects, little attention is paid to possible direct poverty reducing effects. Therefore, we first examine different theoretical direct and indirect ways through which FDI can affect the income of the poor. Wage effects and possible job-creating effects are considered. We find that they depend on the existing human capital and its distribution in society. Following Dollar and Kraay [2000] and Jalilian and Weiss [2001] this hypothesis is confirmed empirically with the use of cross-country regressions for a set of developing countries. In summary, this paper indicates that in developing countries with existing and equally distributed human capital FDI can help fighting poverty whereas in countries with little or very unequally distributed human capital FDI can raise poverty.
Keywords: ddc:330